Training on Artificial Intelligence-Based Chatbot Applications to Improve English Vocabulary Skills for Teachers - Dini Riandini; Reva Marlita; Nova Salma Romadhoni (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This community service activity was motivated by the low ability of teachers at MI Muhammadiyah Kedungwuluh Lor, Patikraja to operate and use Artificial Intelligence-based information technology, in this case chatbots, to support English vocabulary learning. The methods used to carry out this activity included preparation, implementation, and evaluation. The training was attended by 20 participants. It was held at MI Muhammadiyah Kedungwuluh Lor, Patitkraja. The evaluation results showed an increase in the participants' competence after participating in the training activity, with an average post-test score of 90%. This increase reflects the success of the community service program in improving teachers' ability to use chatbots as an information technology-based support medium to assist teachers in more adaptive learning and teaching activities and digital transformation.